Membangun Semangat Belajar dan Nasionalisme dengan Memperkenalkan Budaya Indonesia di Sanggar Bimbingan Kuala Langat: Inculcating a Spirit of Learning and Nationalism through the Introduction of Indonesian Culture at the Sanggar Bimbingan Kuala Langat - Miranti, Dyah; Astutik, Atika Fitri; Rahmawati, Nadia Putri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This article is the result of Community Service Activities, which are a form of implementation of KKN-Dik batch 5 and a form of participation to help fulfill the educational rights of the children of Indonesian Migrant Workers (PMI) in Malaysia as stated in the 1945 Constitution " Berperan dalam mencerdaskan kehidupan bangsa " by applying values -the value of love for the homeland. This service aims to foster the character of love for the homeland in immigrant children in Selangor, namely SB Kuala Langat students. Implementing this service is by applying learning methods in the classroom combined with nationalist values to foster a character attitude of love for the country through learning and playing activities based on nationalist values. The children of immigrant workers still lack the character of love for their homeland, so it is necessary to implement learning methods that foster enthusiasm for learning and increase their sense of love for their country to strengthen their identity as children of the Indonesian nation. The sense of nationalism must always be believed by the children of the Indonesian nation, wherever they are. Therefore, guiding efforts to foster a love for the homeland is very necessary for immigrant children in Selangor, especially for students at the SB Kuala Langat.